Crosstalk Between Epithelial Cells, Neurons and Immune Mediators in HSV-1 Skin Infection - Duarte, Luisa F.; Reyes, Antonia; Farías, Mónica A.; Riedel, Claudia A.; Bueno, Susan M.; Kalergis, Alexis M.; González, Pablo A. (Frontiers in Immunology, 2021)
Herpes simplex virus type 1 (HSV-1) infection is highly prevalent in humans, with approximately two-thirds of the world population living with this virus. However, only a fraction of those carrying HSV-1, which elicits lifelong infections, are symptomatic. HSV-1 mainly causes lesions in the skin and mucosae but reaches the termini of sensory neurons innervating these tissues and travels in a retrograde manner to the neuron cell body where it establishes persistent infection and remains in a latent state until reactivated by different stimuli. When productive reactivations occur, the virus travels back along axons to the primary infection site, where new rounds of replication are initiated in the skin, in recurrent or secondary infections. During this process, new neuron infections occur. Noteworthy, the mechanisms underlying viral reactivations and the exit of latency are somewhat poorly understood and may be regulated by a crosstalk between the infected neurons and components of the immune system. Here, we review and discuss the immune responses that occur at the skin during primary and recurrent infections by HSV-1, as well as at the interphase of latently-infected neurons. Moreover, we discuss the implications of neuronal signals over the priming and migration of immune cells in the context of HSV-1 infection.